Correlation between size of nano-aggregates and excitation wavelength dependent fluorescence emission in room temperature ionic liquids: A case study with emim[FAP] - Anup Ghosh (Elsevier, 2021)
Excitation wavelength dependent emission maximum (400 - 560 nm) of a room temperature ionic liquid has been investigated employing time-resolved fluorescence anisotropy based rotational dynamical analyses. Employing Stokes-Einstein-Debye relationship we could show that nano-aggregate having aggregation volume of ∼250 Å3, ∼350 Å3, ∼400 Å3 and ∼500 Å3 emit at ∼400 nm, ∼450 nm, ∼500 nm, and ∼560 nm respectively.